The use of megaprosthesis in the treatment of proximal and distal femur nonunions in the elderly - Vicenti, Giovanni; Ottaviani, Guglielmo; Carrozzo, Massimiliano; Simone, Filippo; Colasuonno, Giulia; Pesare, Elisa; Trabace, Maddalena; Grasso, Michele; Causo, Francesca; Moretti, Biagio (Lo Scalpello - Journal, 2022)
Management of nonunion in the elderly patient are always a challenge for the orthopedic surgeon. The patient’s clinical condition is often critical, and normal nonunion management strategies are burdened with a high rate of failure. Megaprostheses have been designed for the management of bone tumors, but in the literature many cases of use in non-neoplastic conditions are described. They are, however, burdened by a high rate of complications, and in particular dislocations and periprosthetic infections. Proximal and distal femur replacement should therefore be considered as a salvage strategy to be used in the most severe cases of nonunion in the elderly patient.